Seeing is learning: Vision care for rural and migrant children in China - Yanjie Zhang; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2015)
Uncorrected vision is prevalent among rural children and those who migrate from rural areas to urban areas with their parents in China, of which more than 20 per cent are nearsighted. Since 2012 the Rural Education Action Program (REAP) has carried out the largest empirical vision care project ever conducted in China. More than 20,000 children in different parts of China have been screened and about 5,000 pairs of eyeglasses have been dispensed to those who are nearsighted. REAP has been able to create a comprehensive picture of vision care for rural and migrant children in China. The successfully implemented project so far has provided valuable lessons for treating vision problems. First, wearing eyeglasses can remarkably improve children's educational performance and self-confidence. Second, in contrast to widespread opinion in rural China, eyeglasses are by no means harmful to children's eyesight. Third, and in contrast to another myth, specific 'eye exercises' used as a traditional alternative to eyeglasses cannot slow the onset or progression of myopia. Finally, teacher incentives to encourage children to wear eyeglasses will improve rates of eyeglasses usage, help to overcome vision problems and thus lower educational barriers. Based on these findings, researchers of the project are currently working with local governments in rural China to incorporate vision care into the healthcare agenda.
urn:nbn:de:gbv:3:2-54947
Keywords: 330